Tahsin Method as an Effort of Islamic Religious Education Teachers in Facing Learning Loss - Nurul Hikmah; Mualimin Mualimin (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
This study aims to determine the tahsin method as an effort of Islamic religious education teachers have made at public elementary schools (Sekolah Dasar Negeri, SDN) in Palangka Raya City to deal with learning loss by reciting the Quran post-online learning. The research method was qualitative research with a case study approach. Data collection techniques used interviews, observation, and documentation. The study results showed that the efforts made by Islamic religious education (Pendidikan Agama Islam, PAI) teachers were to provide intensive guidance to students to improve makharijul letters and tajwid from memorizing short surahs that should have been mastered. During online learning, the students were only asked to give memorization via video, and then the teacher gave comments regarding their reading. However, it was less effective in improving their memorization reading of makharijul letters and tajwid. This ability was missing in the PAI subject. So the effort in the form of intensive guidance by using the Quran tahsin method was carried out to repair learning loss or lost abilities in students.